2016
DOI: 10.3168/jds.2016-11110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crude protein level in concentrate supplements on animal performance and nitrogen utilization of lactating dairy cows fed fresh-cut perennial grass

Abstract: Nitrogen pollution of air and ground water from grazing cattle is of increasing concern. Although several studies have investigated mitigation strategies for nitrogen output from dairy cows fed conserved forages and concentrates, similar research on fresh-cut grass in addition to production parameters is limited. The current study, using 3dietary treatments and incorporating 2 genotypes, was designed to evaluate the effects of concentrate crude protein (CP) levels on animal production and nitrogen utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 44 publications
2
29
6
Order By: Relevance
“…Increasing dietary CP from 110.6 g/kg DM to 135.7 g/kg DM should have quantitatively increased the absorption of ruminal NH 3 and therefore consequently increased the urinary N excretion and the total N excretion. The results were in agreement with Hynes et al () who reported that increasing dietary CP levels (14.1, 16.1, 18.1% DM) increased the excretion of the total N and the urinary N in dairy cows. The results indicated that feeding cattle with rations containing the level of CP more than the requirement generally increases the urinary excretion of urea while high urea‐N percentage of the total urinary N and excess intake of CP would lead to the excess excretion of urinary N (Dijkstra et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increasing dietary CP from 110.6 g/kg DM to 135.7 g/kg DM should have quantitatively increased the absorption of ruminal NH 3 and therefore consequently increased the urinary N excretion and the total N excretion. The results were in agreement with Hynes et al () who reported that increasing dietary CP levels (14.1, 16.1, 18.1% DM) increased the excretion of the total N and the urinary N in dairy cows. The results indicated that feeding cattle with rations containing the level of CP more than the requirement generally increases the urinary excretion of urea while high urea‐N percentage of the total urinary N and excess intake of CP would lead to the excess excretion of urinary N (Dijkstra et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicated that the dietary crude protein (CP) level had important impacts on the proportions of N in the faeces and the urine of cattle (Hynes, Stergiadis, Gordon, & Yan, ). At low dietary CP levels, the faeces are the main pathway for N excretion (Castillo et al, ) while at high dietary CP levels the urinary N excretion will be increased in cattle (Marini & Van Amburgh, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the urine N production and urine N-to-total N intake ratio decreased with nor-NOHA and increased with nor-NOHA + Arg compared with control, but the difference was not significant. Furthermore, the output of urea N in milk was also reported to be another NUE indicator closely related to urinary N in animals fed concentrate diets containing different concentrations of CP (Hynes et al, 2016). In present study, the output of MUN also had a nonsignificant tendency to decrease in nor-NOHA + Arg compared with nor-NOHA alone, which partly supported the increased NUE in nor-NOHA + Arg compared with that in nor-NOHA alone.…”
Section: Effects Of Nor-noha Infusion On Digestion Absorption and Usupporting
confidence: 78%
“…Although decreases in dietary CP concentration can increase the risk of restricted microbial activity in the rumen, the PBV values for all diets in this study were still above zero, the recommended minimum allowance (LUKE, 2017). The major increase in manure N excretion can be attributed to urinary N excretion, as observed by Gordon et al (1995) and in other studies with high CP diets (Hynes et al, 2016a(Hynes et al, , 2016b. According to , who reviewed a wide range of dietary treatments (n = 277), on average 84.4% of the incremental N from diets is excreted in urine when using N intake and DMI as independent variables in a bivariate model.…”
Section: Methane Emissions and Energy And N Utilizationmentioning
confidence: 82%